2018
DOI: 10.1016/j.ssc.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Importance of van der Waals interaction on structural, vibrational, and thermodynamic properties of NaCl

Abstract: Thermal equations of state (EoS) are essential in several scientific domains. However, experimental determination of EoS parameters may be limited at extreme conditions, therefore, ab initio calculations have become an important method to obtain them. Density Functional Theory (DFT) and its extensions with various degrees of approximations for the exchange and correlation (XC) energy is the method of choice, but large errors in the EoS parameters are still common. The alkali halides have been problematic from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 90 publications
(119 reference statements)
4
11
0
Order By: Relevance
“… 48 50 Both LC-ωHPBE and ωB97XD are long-range-corrected (ωB97XD additionally has added corrections for atom–atom dispersion interactions), which are required for more accurate description of van der Waals (vdw) interactions during modeling of NaCl crystals. 51 , 52 Along with these functionals, we applied the def2-TZV, def2-TZVP, and def2-TZVPD basis sets 53 , 54 to evaluate the necessity of including polarization or diffuse functions in the basis set. As the def2-TZVPD basis set is not included in the Gaussian library, the basis set parameters were extracted from the Basis Set Exchange database.…”
Section: Computational Methodologymentioning
confidence: 99%
“… 48 50 Both LC-ωHPBE and ωB97XD are long-range-corrected (ωB97XD additionally has added corrections for atom–atom dispersion interactions), which are required for more accurate description of van der Waals (vdw) interactions during modeling of NaCl crystals. 51 , 52 Along with these functionals, we applied the def2-TZV, def2-TZVP, and def2-TZVPD basis sets 53 , 54 to evaluate the necessity of including polarization or diffuse functions in the basis set. As the def2-TZVPD basis set is not included in the Gaussian library, the basis set parameters were extracted from the Basis Set Exchange database.…”
Section: Computational Methodologymentioning
confidence: 99%
“…On the other side, it should be noted that the intrinsic anharmonicity (which will be described in more details in the following discussion, Section 3.4) plays an important role in simulating the thermodynamic properties of minerals at the high-temperature conditions of the deep mantle, such as heat capacities [50,51], P-V-T Equations of State [52,53], equilibrium isotope fractionation at high-P,T condition [54,55], etc. Gillet et al [50] revealed that the anharmonic contribution to the heat capacity of anhydrous forsterite could be as large as 5.5% at 2000 K, while Qin et al [33] and Marcondes et al [56] also pointed out the anharmonic effects might be even more important when weak bonds (such as H bond) are involved.…”
Section: Introductionmentioning
confidence: 99%
“…First, the charge redistribution could lead to a lattice reorganization that reduces strain inhomogeneity, [65,66] which would result in less inhomogeneous broadening. [67] Second, it could result from a reduction of lattice anharmonicity, which is sensitive to dispersion forces [68] that can in turn be modified by screening. [64] We can also study the time dependence of the conductivity after photoexcitation using a 2D scan, which allows us to probe the picosecond evolution of the charge redistribution.…”
Section: Peak-shift and Picosecond Charge Redistribution Dynamicsmentioning
confidence: 99%